Nurses’ Attitudes and Stigma about Mental Illness and Substance Abuse - Šimičić, Mia; Pačarić, Stana; Pavlović, Dragica; Babić, Marko; Farčić, Nikolina; Srb, Nika (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Stigma and negative attitudes can affect the quality of life of the mentally ill and people with substance use disorders. Nurses’ personal attitudes toward mental illness and substance abuse affect the care they provide. AIM: The aim of the study was to examine the attitudes of nurses toward mental illness and substance abuse. MATERIALS AND METHODS: This was a cross-sectional study conducted in March and April 2022 at the Neuropsychiatric Hospital among nurses. The survey was filled out by 100 nurses, 43 (43%) male and 57 (57%) female nurses. The survey consisted of a revised scale for measuring attitudes toward psychiatric patients, the scale of knowledge on psychiatric patients, and the social distance scale. The statistical analysis was performed using MedCalc® Statistical Software version 20.218. RESULTS: Compared to male nurses, female nurses are significantly more afraid of mental patients (χ2 test, p = 0.01), and estimate that they are aggressive and dangerous for the environment (Fisher’s exact test, p = 0.001). Compared to female nurses, male nurses change the way that they communicate significantly more with mentally ill people (χ2 test, p = 0.01, they are especially kind to mentally ill people, so as not to cause unwanted reactions (χ2 test, p < 0.001). CONCLUSION: Nurses’ attitudes toward mentally ill people are negative, and there is a difference according to gender. Most nurses estimate that mentally ill patients are aggressive and dangerous to the environment and cannot fully feel understanding toward them.